PEDAGOGICAL FEATURES OF THE DEVELOPMENT OF THE EDUCATIONAL GOAL - Ortiqova Nargiza Akramovna, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article analyzes the motives for the development of educational characteristics of students in the educational process. Based on the conclusions drawn, the tafflinks are described.